Guide for using “hot potatoes” free software to fortify the teaching learning process to students of fourth level “k” of english major at Technical University of Cotopaxi, during the academic period september 2012 – february 2013. - Ortega Proaño, Marco Enrique (2013)
This research was conducted at Technical University of Cotopaxi with students of fourth level “K” of English Major. It is located in Eloy Alfaro parish, Latacunga city, Cotopaxi province, in the neighborhood called “El Ejido”. This is a public institution of Higher Education, free and lay, and was created on January 24th, 1995 by law enacted in the Official Register No. 618. The English teaching learning process at Technical University of Cotopaxi has an important place into the students’ education because it permits to communicate effectively among people, but the shortage of laboratories, software or user’s guide causes many difficulties in the learning of communicative skills like listening, speaking, reading and writing. The method used for this investigation work was the descriptive because it permitted to make an identification of the present situation related to the use of “Hot Potatoes” software in the English learning. The main objective of this research was to elaborate a guide for using “Hot Potatoes” free software to fortify the teaching learning process. The guide contents an explanation about each application such as JQuiz, JMatch, JCross, JMix and JCloze and includes images, pictures and all of the necessary steps in order to facilitate its comprehension and the creation of quizzes, workshops, tasks or simply feedback for students. Finally, the contribution of this research was to change the way that teachers and students think about the use of technology. Education with technology produces positive effects on students and changes the attitudes toward English learning.